GAMMA-AMINOBUTYRIC ACID (GABA): PHYSICOCHEMICAL PROPERTIES AND ITS SIGNIFICANCE IN MEDICINE. - Khaydarova H.A., (Ustozlar uchun, 2025)
Annotation. Gamma-aminobutyric acid (GABA) is one of the most important naturally occurring amino acids in the human body. It functions primarily as the chief inhibitory neurotransmitter within the central nervous system (CNS). Discovered in the mid-20th century, GABA’s primary role is to reduce neuronal excitability, thus maintaining the balance between excitation and inhibition essential for normal brain function. Beyond its neurological function, GABA exhibits numerous physiological effects, and its derivatives and analogs are increasingly used in medicine. This essay provides a detailed analysis of the physicochemical properties of GABA, its biological significance, and its applications in the medical and pharmaceutical fields.